2009
DOI: 10.1063/1.3259922
|View full text |Cite
|
Sign up to set email alerts
|

Strong Tc dependence for strained epitaxial Ba(Fe1−xCox)2As2 thin films

Abstract: Normal metal-superconductor decoupling as a source of thermal fluctuation noise in transition-edge sensors J. Appl. Phys. 112, 034515 (2012) Transport critical-current density of superconducting films with hysteretic ferromagnetic dots AIP Advances 2, 022166 (2012) Pressure effects on strained FeSe0.5Te0.5 thin films J. Appl. Phys. 111, 112610 (2012) Magnetoresistance and transistor-like behavior of a double quantum-dot via crossed Andreev reflections J. Appl. Phys. 111, 113905 (2012) What are the intern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 19 publications
6
112
0
Order By: Relevance
“…A sharp superconducting transition at T c = 26.5 K was observed with a small transition width of ΔT c = 1.5 K, which is consistent with the slightly underdoped P-concentration determined by EPMA [P/(As + P) = 22%]; however, this T c is 15 K higher than that of a single crystal with the same P concentration and is comparable to that of a 27% P-doped single crystal. [22] As mentioned above, a tensile strain in the ab plane is introduced into the BaFe 2 As 2 :P epitaxial films, which suggests that the effect of the tensile strain is opposite to an optimally doped BaFe 2 As 2 :Co epitaxial film because a tensile strain decreases T c for BaFe 2 As 2 :Co [23] . On the other hand, it was recently reported that a tensile strain in a BaFe 2 As 2 :P epitaxial film shifts its optimum doping level to an underdoped region [24] .…”
Section: Junction Devicesmentioning
confidence: 99%
“…A sharp superconducting transition at T c = 26.5 K was observed with a small transition width of ΔT c = 1.5 K, which is consistent with the slightly underdoped P-concentration determined by EPMA [P/(As + P) = 22%]; however, this T c is 15 K higher than that of a single crystal with the same P concentration and is comparable to that of a 27% P-doped single crystal. [22] As mentioned above, a tensile strain in the ab plane is introduced into the BaFe 2 As 2 :P epitaxial films, which suggests that the effect of the tensile strain is opposite to an optimally doped BaFe 2 As 2 :Co epitaxial film because a tensile strain decreases T c for BaFe 2 As 2 :Co [23] . On the other hand, it was recently reported that a tensile strain in a BaFe 2 As 2 :P epitaxial film shifts its optimum doping level to an underdoped region [24] .…”
Section: Junction Devicesmentioning
confidence: 99%
“…30 In contrast, at high pulse energy, the DR was too high to complete the surface reconstruction, leading to the increased FWHMs with increasing pulse energy, completing the inverted bell-like shape of the FWHM. Iida et al 28,29 also reported epitaxial growth of Ba(Fe,Co) 2 As 2 films using a KrF excimer laser, but they need to use a Fe buffer layer to obtain good epitaxial films. This would be because that their laser power was in the range of 3-5 J/cm 2 , which is much lower than our optimum values (see Table I), and their substrate-to-target distance was longer (50 mm) than that of our PLD growth chamber (30 mm); therefore, we speculate that the above-discussed supersaturation regime is not attained due to the low density and the low kinetic energies of the deposition precursors, and consequently the Fe buffer layer is required to assist improved epitaxial growth.…”
mentioning
confidence: 99%
“…By means of spin rotation method, it was confirmed that a static magnetic order might emerge above at applied pressure non transiting the 122-family [13][14][15], high-quality mono crystals of 1111 family and FeSe are small are usually plate-like measuring a few hundreds of micrometer across and tens of micrometer thick [16][17][18]. In this esteem, the preparation of high quality thin film samples not only satisfies the requirements for some fundamental physical properties measurements other than also provides appropriate bases for making tunneling junctions that resolves more than a few imperative superconducting parameters such as gap value and paring equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it was also told that superconducting Thin films of Sr (Fe 1−x Cox) 2 As 2 and Ba(Fe 1−x Co x ) 2 As 2 , correspondingly, while thin films of FeSe, Ferrous Telenide (FeTe) and FeSe 1−x Te x were as well revealed to have superconductivity. In recent times, The first superconducting epitaxial LaFeAsO 1−x Fx thin film with analogous Tc to that of bulk, by growing at room temperature followed with 7h post annealing at 960°C in vacuum [17][18][19].…”
Section: Introductionmentioning
confidence: 99%